The effect of wetting area in carbon paper electrode on the performance of vanadium redox flow batteries: A three-dimensional lattice Boltzmann study - Zhang,D; Cai,Q; Taiwo,OO; Yufit,V; Brandon,NP; Gu,S (Electrochimica Acta, 2018)
The vanadium redox flow battery (VRFB) has emerged as a promising technology for large-scale storage of intermittent power generated from renewable energy sources due to its advantages such as scalability, high energy efficiency and low cost. In the current study, a three-dimensional(3D) Lattice Boltzmann model is developed to simulate the transport mechanisms of electrolyte flow, species and charge in the vanadium redox flow battery at the micro pore scale. An electrochemical model using the Butler-Volmer equation is used to provide species and charge coupling at the surface of active electrode. The detailed structure of the carbon paper electrode is obtained using X-ray Computed Tomography(CT). The new model developed in the paper is able to predict the local concentration of different species, over-potential and current density profiles under charge/discharge conditions. The simulated capillary pressure as a function of electrolyte volume fraction for electrolyte wetting process in carbon paper electrode is presented. Different wet surface area of carbon paper electrode correspond to different electrolyte volume fraction in pore space of electrode. The model is then used to investigate the effect of wetting area in carbon paper electrode on the performance of vanadium redox flow battery. It is found that the electrochemical performance of positive half cell is reduced with air bubbles trapped inside the electrode.